Performance Evaluation Fuzzy Logic Control on Low-Cost Medical Equipment Sterilizer - Alex Wenda (JINAV: Journal of Information and Visualization, 2022)
The equipment is not sterile when the health equipment is used repeatedly. Thus, it is at risk of infection. Data published by WHO reveals that one out of every ten hospital patients gets an infection. In developed countries, the number of infected hospital patients reaches 30%, while in developing countries it is at least 2-3 higher. One way to reduce the occurrence of infection is to sterilize medical equipment through a dry heat sterilization process at 1700 C for 60 minutes. The high price of sterilizers means that many health centers and clinics do not have this equipment. The aim of this study was to design a low-cost dry heat type health equipment sterilizer using fuzzy logic as a controller and evaluate the performance of the controller. Regarding to the research result, it indicated that the controller performance evaluation was very good with the highest overshoot value of 1.1%, the steady state error value was 1.1%, and the fastest rise time was 240 seconds.